Antibiotic prescribing pattern among paediatric patients attending tertiary care hospital in South India - Priyadharsini, R. P.; Kesavan, R. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The usage of antibiotics among paediatric age group in India is on the higher side, that more than 60% of children in the age group 0 to 4 years received antibiotics. The higher use of antibiotics results in antibiotic resistance, increased health care costs, adverse drug reaction and may complicate the treatment of infections in future. There is a continuous need to monitor the prescription of antibiotics at all health care levels to prevent antibiotic resistance. Methods: A prospective and descriptive study was conducted in one of the pharmacies which dispenses the paediatric prescriptions in a tertiary hospital. The prescriptions used to treat infection were collected and analysed. A total of 500 prescriptions were collected and analysed. Results: The prescriptions were analysed for the WHO prescribing indicators. The average number of drugs per prescription is 1.84 with 21% of the prescriptions containing antibiotics. The most commonly prescribed antibiotics were penicillin like amoxycillin, phenoxymethyl penicillin followed by cotrimoxazole and cephalosporin group of antibiotics. The antibiotics prescribed belonged to the access group of antibiotics. The percentage of the prescriptions with drugs form essential drugs list and prescribed with generic name is 65.8% and 67% respectively. There were no injections prescribed. Conclusions: The antibiotic prescribing pattern and the average drugs per prescription falls with the WHO range indicating reduced use of antibiotics and absence of polypharmacy. However, the prescription of generic drugs and the drugs from the essential drug list is less.